Knowledge and Attitude of Health Care Providers on the Use of Partogram: A Study in Rural Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Background: This study was conducted to assess the knowledge and attitude of health care providers regarding effective use of the partogram in monitoring the progress of labour.Methods: A total fifty health care providers were assessed with a preformed questionnaire during pre and post exposure to a 5-day training program and their pre- and post-test scores were analyzed. Attitude was assessed by checking randomly selected 50 partographs filled up by trained health care providers. Their attitude also tested by direct interviewing with 50 service providers.Results: Mean age of the respondents was 31.22 (±6.32) years. There was significant improvement of test scores after the training program. Random partograph assessment showed 85.4% correct response. Majority respondents showed positive attitude towards the use of partograph.Conclusion: Results of this study shows that the 5-day training program on use of partograph is effective. But further training programs including refresher training and capacity building on programme is required for long term success on the use of partograph.Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 99-105